Notion of Strategic Control - Sejdija, Qemajl (European Journal of Multidisciplinary Studies, 2016)
With strategic control, we understand the special type of strategic control which is aimed to monitoring and evaluation of strategic management process in order to ensure its functioning and progress. In fact, the strategic control is applied to ensure if all the planned results are accomplished during the process of strategic management. The basic purpose of strategic control is to assist senior management in achieving the objectives of the enterprise with the assistance of monitoring and evaluation of strategic management in general, and particularly in the implementation of the selected strategy. Relying on the preliminary explanation, the results of the assessments are reflected in the strategic management of the enterprise environment, the establishment of vision, mission and goals of the strategy and the conversion of strategy into shares. Strategic control in this case appears as a reverse link that provides feedback to determine whether all stages of the process of strategic management and how they function have been implemented in harmony.
Keywords: Notion of Strategic Control